ANALISIS DATA PENETRASI PASAR MODERN TERHADAP PENDAPATAN PEDAGANG PASAR TRADISIONAL BATUJAJAR - Mizani, Mohamad; Ma’mun, Saepul; Sutira, Andri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
This research is motivated by the rapid growth of modern markets (minimarkets) in Batujajar District which has led to a decrease in the income of traditional market traders. The purpose of this study is to examine the influence of modern markets on the income of traditional market traders. This study uses a quantitative approach with a survey method through a questionnaire. The research population consisted of 800 market traders, with a saturated sample of 90 traders from the Batujajar Traditional Market who filled out questionnaires related to modern market variables and traders' income. The results of the study show that modern market variables have a normal distribution with a high category, while the trader's income variable is in the medium category. The product-moment correlation analysis yielded a coefficient of 0.526 with the medium category, and the R Square value in the regression model was 0.277, showing that 27.7% of the variation in traders' income was explained by modern market variables. The regression equation obtained is Y = 14.908 + 0.663X. The results of the hypothesis test showed a t-value of 5.803 with a significance of 0.000, which was below alpha 5%, so the alternative hypothesis was accepted. In conclusion, modern markets contribute significantly to the decline in the income of traditional market traders in Batujajar District.